Synthesis and characterization of new injectable and degradable dextran-based hydrogels - Maia, João (2005)
Injectable and degradable hydrogels are very interesting networks for drug delivery and cell transplantation applications since they can be administered in the human body in a minimally invasive way. In most cases, the crosslinking reaction occurs by photopolymerisation or free radical polymerisation; however, the use of chemical initiators may promote cell death. In the current work, injectable and degradable dextran-based hydrogels were prepared without the use of initiators. Dextran, a natural glucose-containing polysaccharide, was oxidized with sodium periodate (dexOx) and the derivatives characterized by NMR and FTIR spectroscopy's as well as by colorimetric techniques. The oxidized derivatives were crosslinked with adipic acid dihydrazide (AAD), forming a gel within 2-4 min. The obtained hydrogels were characterized by their mechanical properties, swelling and degradation behavior under physiologic conditions. In addition, the hydrogel interior morphology as well as porous structure was evaluated by scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP). MIP analysis showed that dexOx hydrogels crosslinked with 10% of AAD were macroporous with pore sizes ranging from 0.32 to 0.08 [mu]m. As expected, the average pore size increased during hydrogel degradation as confirmed by SEM and MIP studies.